A Multicenter Evaluation of Different Chemotherapy Regimens in Older Adults With Head and Neck Squamous Cell Carcinoma Undergoing Definitive Chemoradiation - Rühle, Alexander; Weymann, Maria; Behrens, Max; Marschner, Sebastian; Haderlein, Marlen; Fabian, Alexander; Senger, Carolin; Dickstein, Daniel R.; Kraft, Johannes; von der Grün, Jens; Chen, Eric; Aquino-Michaels, Todd; et al. (International Journal of Radiation Oncology Biology Physics, 2024)
Purpose: The number of older adults with head and neck squamous cell carcinoma (HNSCC) is increasing, and treatment of these patients is challenging. Although cisplatin-based chemotherapy concomitantly with radiation therapy is considered the standard regimen for patients with locoregionally advanced HNSCC, there is substantial real-world heterogeneity regarding concomitant chemotherapy in older patients with HNSCC. Methods and Materials: The SENIOR study is an international multicenter cohort study including older patients (≥65 years) with HNSCC treated with definitive radiation therapy at 13 academic centers in the United States and Europe. Patients with concomitant chemoradiation were analyzed regarding overall survival (OS) and progression-free survival (PFS) via Kaplan-Meier analyses. Fine‐Gray competing risk regressions were performed regarding the incidence of locoregional failures and distant metastases. Results: Six hundred ninety-seven patients with a median age of 71 years were included in this analysis. Single-agent cisplatin was the most common chemotherapy regimen (n = 310; 44%), followed by cisplatin plus 5-fluorouracil (n = 137; 20%), carboplatin (n = 73; 10%), and mitomycin C plus 5-fluorouracil (n = 64; 9%). Carboplatin-based regimens were associated with diminished PFS (hazard ratio [HR], 1.39 [1.03-1.89]; P < .05) and a higher incidence of locoregional failures (subdistribution HR, 1.54 [1.00-2.38]; P = .05) compared with single-agent cisplatin, whereas OS (HR, 1.15 [0.80-1.65]; P = .46) was comparable. There were no oncological differences between single-agent and multiagent cisplatin regimens (all P > .05). The median cumulative dose of cisplatin was 180 mg/m2 (IQR, 120-200 mg/m2). Cumulative cisplatin doses ≥200 mg/m2 were associated with increased OS (HR, 0.71 [0.53-0.95]; P = .02), increased PFS (HR, 0.66 [0.51-0.87]; P = .003), and lower incidence of locoregional failures (subdistribution HR, 0.50 [0.31-0.80]; P = .004). Higher cumulative cisplatin doses remained an independent prognostic variable in the multivariate regression analysis for OS (HR, 0.996 [0.993-0.999]; P = .009). Conclusions: Single-agent cisplatin can be considered in the standard chemotherapy regimen for older patients with HNSCC who can tolerate cisplatin. Cumulative cisplatin doses are prognostically relevant in older patients with HNSCC.
CRIS-Team Scopus Importer:2024-01-12

Cell-In-Cell Structures in Early Breast Cancer Are Prognostically Valuable - Bauer, Mareike; Hildebrand, Laura; Rosahl, Marie-Charlotte; Erber, Ramona; Schnellhardt, Sören; Büttner-Herold, Maike; Putz, Florian; Ott, Oliver; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
Cell-in-cell (CIC) structures in breast cancer have so far been studied in a small inhomogeneous patient population, suggesting the prognostic importance of CIC. In the present study, we focused on CIC in early hormone-sensitive breast cancer. With in vitro co-culture experiments, we compared the homotypic phagocytic capacity of two breast cancer cell lines to that of primary human fibroblasts. Afterward, we studied 601 tissue specimens from 147 patients participating in an institutional accelerated partial breast irradiation (APBI) phase II trial. Both breast cancer cell lines performed non-professional phagocytosis at a higher rate than primary human fibroblasts. In this study cohort, 93.2% of the patients had T1 tumours, and 6.8% had T2 tumours. CIC was found in 61.2% of the patients, with a CIC rate ranging from <1/mm2 to 556.5/mm2 with a mean of 30.9/mm2 ± 68.4/mm2. CIC structures were prognostically favourable for local recurrence-free survival and disease-free survival. Regarding metastasis-free survival, CIC-positive patients had an unfavourable prognosis. Subgroup analysis indicated a correlation between a high proliferation index and high CIC rates. CIC had the highest prognostic value in young breast cancer patients (p = 0.004). With this study, we provide further evidence of CIC as a prognostic marker in breast cancer.
CRIS-Team Scopus Importer:2023-01-20
Keywords: accelerated partial breast irradiation; breast cancer; cell-in-cell; ionizing radiation; non-professional phagocytosis; radiotherapy

Evaluation of Concomitant Systemic Treatment in Older Adults With Head and Neck Squamous Cell Carcinoma Undergoing Definitive Radiotherapy - Rühle, Alexander; Marschner, Sebastian; Haderlein, Marlen; Fabian, Alexander; Weymann, Maria; Behrens, Max; Senger, Carolin; Dickstein, Daniel R.; Kraft, Johannes; von der Grün, Jens; Chen, Eric; Aquino-Michaels, Todd; et al. (JAMA Network Open, 2023)
Importance: The number of older adults with head and neck squamous cell carcinoma (HNSCC) is increasing, and these patients are underrepresented in clinical trials. It is unclear whether the addition of chemotherapy or cetuximab to radiotherapy is associated with improved survival in older adults with HNSCC. Objective: To examine whether the addition of chemotherapy or cetuximab to definitive radiotherapy is associated with improved survival in patients with locoregionally advanced (LA) HNSCC. Design, Setting, and Participants: The Special Care Patterns for Elderly HNSCC Patients Undergoing Radiotherapy (SENIOR) study is an international, multicenter cohort study including older adults (≥65 years) with LA-HNSCCs of the oral cavity, oropharynx/hypopharynx, or larynx treated with definitive radiotherapy, either alone or with concomitant systemic treatment, between January 2005 and December 2019 at 12 academic centers in the US and Europe. Data analysis was conducted from June 4 to August 10, 2022. Interventions: All patients underwent definitive radiotherapy alone or with concomitant systemic treatment. Main Outcomes and Measures: The primary outcome was overall survival. Secondary outcomes included progression-free survival and locoregional failure rate. Results: Among the 1044 patients (734 men [70.3%]; median [IQR] age, 73 [69-78] years) included in this study, 234 patients (22.4%) were treated with radiotherapy alone and 810 patients (77.6%) received concomitant systemic treatment with chemotherapy (677 [64.8%]) or cetuximab (133 [12.7%]). Using inverse probability weighting to attribute for selection bias, chemoradiation was associated with longer overall survival than radiotherapy alone (hazard ratio [HR], 0.61; 95% CI, 0.48-0.77; P < .001), whereas cetuximab-based bioradiotherapy was not (HR, 0.94; 95% CI, 0.70-1.27; P = .70). Progression-free survival was also longer after the addition of chemotherapy (HR, 0.65; 95% CI, 0.52-0.81; P < .001), while the locoregional failure rate was not significantly different (subhazard ratio, 0.62; 95% CI, 0.30-1.26; P = .19). The survival benefit of the chemoradiation group was present in patients up to age 80 years (65-69 years: HR, 0.52; 95% CI, 0.33-0.82; 70-79 years: HR, 0.60; 95% CI, 0.43-0.85), but was absent in patients aged 80 years or older (HR, 0.89; 95% CI, 0.56-1.41). Conclusions and Relevance: In this cohort study of older adults with LA- HNSCC, chemoradiation, but not cetuximab-based bioradiotherapy, was associated with longer survival compared with radiotherapy alone.
CRIS-Team Scopus Importer:2023-03-10

Expression of Immune Phenotypes in Rectal Cancer after neoadjuvant Chemoradiotherapy - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-dose radiotherapy of osteoarthritis: from biological findings to clinical effects-challenges for future studies - Weissmann, Thomas; Rückert, Michael; Putz, Florian; Donaubauer, Anna-Jasmina; Hecht, Markus; Schnellhardt, Sören; Schubert, Philipp; Roesch, Johannes; Höfler, Daniel; Ott, Oliver; Haderlein, Marlen; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2023)

Neutrophils in HNSCC Can Be Associated with Both a Worse or Favorable Prognosis - Brunkhorst, Hendrik; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (Biomolecules, 2024)
The prognostic significance of tumor-infiltrating neutrophils in head and neck squamous cell carcinoma (HNSCC) is poorly understood. It is unclear how the presence of neutrophils affects prognosis due to their polarization into cytotoxic N1 or immunosuppressive N2. Therefore, we determined the number of CD66b+ neutrophil granulocytes separately in the stromal and epithelial compartments in cancer tissues from 397 patients with HNSCC. Tumor samples from six historical patient groups were processed into tissue microarrays and stained immunohistochemically. In total, 21.9% were HPV positive (p16+). Neutrophil counts were much lower in the stromal compartment (372 ± 812) than in the epithelial cancer compartment (1040 ± 1477) (p < 0.001), with large differences between groups. In three groups with high neutrophil infiltration, high rates were associated with a favorable prognosis, whereas in two groups, high rates were a negative prognostic factor. In p16- oropharyngeal and hypopharyngeal cancer high infiltration was associated with a favorable prognosis. Cancers with an exclusion of neutrophils in the epithelial compartment were associated with improved prognosis. In oropharyngeal and hypopharyngeal HPV-negative cancer high neutrophil infiltration rates were clearly associated with prolonged survival. Neutrophil granulocytes in HNSCC may contribute to a favorable or unfavorable prognosis.
CRIS-Team Scopus Importer:2024-03-08
Keywords: CD66b+; head and neck cancer; HNSCC; hypopharynx; larynx; neutrophils; oral cavity; oropharynx; prognosis; tumor-associated neutrophils

Predicting cisplatin tolerability in older adults with head and neck cancer – Insights for improved chemoradiation outcomes - Rühle, Alexander; Weymann, Maria; Behrens, Max; Olbrich, Johannes; Kut, Carmen; Marschner, Sebastian N.; Haderlein, Marlen; Fabian, Alexander; Senger, Carolin; Bakst, Benjamin P.; Kraft, Johannes; von der Grün, Jens; et al. (Radiotherapy and Oncology, 2025)
Purpose: Cumulative cisplatin doses of ≥ 200 mg/m2 improve survival in adults with head-and-neck squamous cell carcinoma (HNSCC) undergoing chemoradiation, but many older adults with HNSCC cannot receive this prognostically relevant dose due to toxicities. This study aims to develop predictive models to assess the likelihood of older adults with HNSCC receiving ≥ 200 mg/m2 cisplatin during chemoradiation. Methods: 366 patients from the SENIOR database, an international cohort of adults ≥ 65 years with HNSCC, received definitive chemoradiation with single-agent cisplatin and were analyzed. A Generalized Linear Model (GLM), Support Vector Machine (SVM), and Random Forest Model (RFM) were trained and compared for their performance in predicting a cumulative cisplatin dose of ≥ 200 mg/m2. Results: 195 (53 %) patients achieved a cumulative cisplatin dose of ≥ 200 mg/m2. In the GLM, laryngeal carcinoma (β = 1.37, p = 0.01), tumoral p16 positivity (β = 0.69, p = 0.04), higher hemoglobin levels (β = 0.26, p = 0.002), elevated C-reactive protein (CRP) concentration (β = 0.02, p = 0.003), and increased estimated glomerular filtration rate (eGFR) (β = 0.02, p = 0.008) were associated with a higher probability of reaching ≥ 200 mg/m2 cisplatin. Hemoglobin, CRP, eGFR, and p16 status constituted the most important features in the SVM and RFM. AUC values for the GLM, SVM, and RFM were 0.70 (95 % CI, 0.67–0.73), 0.71 (95 % CI, 0.68–0.73), and 0.73 (95 % CI, 0.71–0.75), respectively. Conclusions: We developed predictive models to support clinicians in identifying older adults with HNSCC capable of tolerating ≥ 200 mg/m2 cumulative cisplatin during chemoradiation. Once validated, these models could improve personalized treatments and enhance shared decision-making in older adults with HNSCC.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chemotherapy; Cisplatin; Elderly; Geriatric; Head-and-neck cancer; Radiotherapy

Shifts in Macrophage as a prognostic Biomarker in Patients with luminal Breast Cancer - A Confirmatory Study - Schnellhardt, Sören; Segelhorst, Sarah; Erber, Ramona; Daniel, Christoph; Hartmann, Arndt; Fasching, Peter; Beckmann, Matthias; Fietkau, Rainer; Distel, Luitpold; Rübner, Matthias (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The Prognostic and Predictive Significance of Tumor-Infiltrating Memory T Cells Is Reversed in High-Risk HNSCC - Hartan, Rebekka; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cells, 2022)
Tumor-infiltrating CD45RO+ memory T cells have unanimously been described as a positive prognostic factor in head and neck squamous cell carcinomas (HNSCCs). Here, we investigated the long-term prognostic relevance of CD45RO+ memory T cells in HNSCC with special regard to the influence of clinical characteristics. Pre-treatment biopsy samples from 306 patients with predominantly advanced HNSCC were analyzed. Immunohistochemistry was used to stain tissue microarrays for CD45RO+ memory T cells. CD45RO cell densities were semi-automatically registered and used for survival analysis. High CD45RO+ cell densities were clearly associated with prolonged overall survival (OS) and recurrence-free survival as well as no evidence of disease status after 10 years (p < 0.05). In contrast, the prognostic significance of tumor-infiltrating memory T cells was completely reversed in high-risk groups: in poorly differentiated tumors (G3, G4) and in cases with lymph node involvement (N+), high memory T cell densities correlated with reduced 10-year OS (p < 0.05). In conclusion, an increased density of tumor-infiltrating CD45RO+ cells in HNSCC can be a positive as well as a negative prognostic factor, depending on disease stage and histological grade. Therefore, if CD45RO+ cell density is to be used as a prognostic biomarker, further clinical characteristics must be considered.
CRIS-Team WoS Importer:2022-07-08
Keywords: CD45RO; head and neck cancer; memory T cells; prognostic value; reversal of prognostic value

The prognostic Relevance of tumor infiltrating Inflammatory Cells in early Breast Cancer - Schnellhardt, Sören (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

The Prognostic Value of FoxP3+Tumour-Infiltrating Lymphocytes in Rectal Cancer Depends on Immune Phenotypes Defined by CD8+Cytotoxic T Cell Density - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Frontiers in Immunology, 2022)
Tumour-infiltrating FoxP3+ regulatory T cells have been identified as both positive and negative prognostic factors in colorectal cancer (CRC) and rectal cancer (RC). In this study we investigated whether immune phenotypes, defined by CD8+ cytotoxic T cell density, may influence the prognostic association of FoxP3+ T cell densities in RC. Tissue microarrays from 154 rectal cancer resections were immunohistochemically double stained for CD8 and FoxP3. CD8+ and FoxP3+ cell densities were measured in the stromal and intraepithelial compartment. Stromal FoxP3+ cell densities were not associated with 10-year overall survival (OS). In the "immune-desert" phenotype, defined by very low stromal CD8+ cell density, a high density of stromal FoxP3+ T cells displayed a tendency towards an association with decreased 10-year OS (p = 0.179). In "inflamed" tumours, defined by high intraepithelial CD8+ T cell infiltration, the opposite was the case and high stromal FoxP3+ T cell densities were a positive prognostic factor (p = 0.048). Additionally, patients with an increased FoxP3/CD8 cell density ratio demonstrated a strong trend towards decreased 10-year OS (p = 0.066). These contrasting findings suggest functional heterogeneity within the group of FoxP3+ T cells. They are consistent with experimental studies which reported suppressive and non-suppressive populations of FoxP3+ T cells in CRC. Furthermore, our study demonstrates that CD8 immunohistochemistry may act as an instrument to identify tumours infiltrated by possibly functionally differing FoxP3+ T cell subtypes.
CRIS-Team WoS Importer:2022-02-18

Tumor Infiltrating Inflammatory Cells as a prognostic Factor in Glioblastoma - Schnellhardt, Sören; Zorob, Alexander; Polat, B.; Lisowski, D.; Daniel, Christoph; Monoranu, C-M; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Tumor-infiltrating Memory T Cells in Head and Neck Tumors: An ambivalent prognostic Factor - Hartan, R.; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16